Quantum modelling of organic materials for electronics, thermoelectric, and photoluminescent applications / Mohamad Syafie Mahmood - Mohamad Syafie , Mahmood (2018)
Organic semiconductors are dominating a niche segment of applications in electronic devices, as an alternative to inorganic semiconductors. They are becoming mainstream in electronic devices such as organic light emitting diode (OLED) and nanowires due to their promising advantages such as low cost, ease of synthesis and high throughput fabrication methods. In this thesis, 3 families of organic materials; discotic liquid crystal (DLC), protic ionic liquid (PIL), and chalcone are chosen for their potential applications in electronics, thermoelectric, and fluorescence respectively. Therefore, this work is separated into 3 corresponding major sections as follows; (1) correlation between molecule structure and electronic properties of the 2,3,6,7,10,11-hexahexyloxytriphenylene (HAT6) DLC molecule using first principle Density Functional Theory (DFT), (2) quantum thermodynamic calculations of entropy for amine based PILs, and (3) photoluminescent efficiency evaluation of 4-dimethylamino-2ʹ-hydroxychalcone (DHC) based on molecular conformation. In (1), the columnar stacking of HAT6 molecules allows π-π orbital overlap at the molecular core which allows electronic charge transfer along the column. The electronic transfer is affected by conformation of DLC molecules in columnar phases, namely core-core facial separation (D), angular twist (θ), and lateral slide (L). The correlation between molecular structure and electronic properties are evaluated in terms of its formation energy, band gap (BG), and density of state (DOS). The preservation of π-π interaction by maintaining the integrity of its columnar structural characteristics is key to maintaining the DLC’s charge transfer efficacy. In (2), quantum thermodynamic simulation of a series of amine based PILs (ethylammonium triflate (EaTf), diethylammonium triflate (DieaTf), triethylammonium triflate (TrieaTf), and 2-methylpyridinium triflate (2mpTf)) was carried out to calculate the entropy of the system. Analysis in terms of vibrational and conformational contribution to entropy was then extended to evaluate the role of PIL in a thermoelectric solution. In this section, the focus is on the vibration of proton attachment, which has the biggest influence on their thermodynamic properties. Then, a hypothetical thermodynamic cycle is built around the states where the thermodynamic-conformation mechanism was discussed. Thus, the relationship between molecule properties to the thermoelectric properties such as Seebeck coefficient was elucidated. In (3), the photoluminescence capability of the DHC from the chalcone family was evaluated using first principle DFT calculation. The conformation of the DHC in the ground and excited states were evaluated in crystalline state and in solutions. The conservation of planarity in the ground to excited state are expected to provide large photoluminescence yield. In solution, it is shown that the minimum energy in the excited state are achieved by a twist in the conformation, this provided a non-radiative pathway which quenches photoluminescence. In the crystalline state, the calculations show that the planarity is conserved going from the ground to excited state which encourage a high quantum yield of photoluminescence. These simulations are strongly supported by femtosecond spectroscopy results and provide a promising pathway for the use of chalcone in optoelectronic/bioimaging applications. Thus, this thesis provides a pathway for molecular design using first principle DFT calculations, to provide an optimisation strategy of better organic electronic materials for applications in electronics, thermoelectric, and optoelectronic.